Pengaruh Self-Compassion dan Self-Esteem Terhadap Perilaku Cyberbullying pada Mahasiswa Teknologi Informasi - Winda Rahmadita; Tiara Nur Febrianiza; Tirsa Marisa; Alexio Alexio; Nur Muhamad Imana (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to determine: (1) Description of Self-compassion, Self-esteem, and Cyberbullying in Education Study Program students Information Technology at IKIP PGRI Pontianak, (2) The influence of self-compassion on Cyberbullying behavior in Study Program students Information Technology Education in IKIP PGRI Pontianak, (3)The influence of self-esteem on cyberbullying behavior in students Information Technology Education Study Program at IKIP PGRI Pontianak, (4) The influence of Self-compassion and Self-esteem together on Cyberbullying behavior in Education Study Program students Information Technology in IKIP PGRI Pontianak. Which method used in this study is quantitative. Data is retrieved through spread questionnaire (questionnaire) to 135 students. The results of this study show that: (1) There is no effect of Self-compassion on behavior Cyberbullying on Information Technology Education Study Program students at IKIP PGRI Pontianak environment, (2) There is no effect of Self-esteem on Cyberbullying behavior in Education Study Program students Information Technology in the Pontianak PGRI IKIP environment, (3) Not available the effect of Self-compassion and Self-esteem together on behavior Cyberbullying on Information Technology Education Study Program students at IKIP PGRI Pontianak environment.